The aesthetic theory of Arabic calligraphy (Journal of the College of Basic Education, 2022)
The current research dealt with (aesthetic theory in Arabic calligraphy - Thuluth calligraphy as a model -) in an attempt to study the aesthetic qualities of Arabic calligraphy letters that were inspired by Islamic art with its constructive conceptual references and to benefit from the characteristic of aesthetic letters according to formations with relationships centered in the structure of calligraphic work in the form of ideas and contents (text ) were employed, and referred from its functional (notational) specificity to aesthetic (decorative) privacy envisaged by the rules of Arabic letters and their origins, as the Arabic calligraphy was associated with the Qur’anic texts and the noble hadiths of the Prophet and the stages of their improvement functionally and aesthetically